The relationships between university students' physical activity levels, insomnia and psychological well-being - EROL, SAİME (KARE PUBL, 2020)
Objectives: This study aims to determine university students' physical activity levels, insomnia and psychological well-being, and to examine the relationships between them. Methods: This descriptive and correlation-seeking research's sample included 702 voluntarily participating students studying in the faculty of health sciences and the faculty of science and letters at a university. The data were collected using a 23-item participant information form, the International Physical Activity Questionnaire (IPAQ), the Bergen Insomnia Scale (BIS) and the Psychological Well-being Scale (PWBS). Descriptive statistics, the Mann-Whitney U test, the Kruskal-Wallis test, the chi-squared test, logistic regression analysis and the Games-Howell post hoc test were used to evaluate the data. Results: Of the students, 20.4% were inactive, 57% were minimally active, and 22.6% were sufficiently active. Of them, 59.3% had insomnia. The participants' PWBS scores were above average (40.23 +/- 8.18). The students who described themselves as having a bad psychological state had more insomnia, and a one point increase in the PWBS score reduced the risk of insomnia by a factor of 0.972. The students with bad family relationships had increased risk of insomnia by a factor of 1.512, the students who had continual headaches had increased risk of insomnia by a factor of 2.504, and the students who used phones in bed had increased risk of insomnia by a factor of 1.760. Conclusion: High physical activity levels increased psychological well-being, and high psychological well-being scores, good family relationships and regular physical activity reduced insomnia.
Keywords: Insomnia; physical activity; psychological well-being; university students; SOCIAL SUPPORT; SLEEP PROBLEMS; ASSOCIATION; SYMPTOMS; VALIDITY; QUALITY; HEALTH